PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI SERVICE QUALITY SEBAGAI VARIABELINTERVENING PADA PERUSAHAAN PERBANKAN DI SURABAYA - Putra, Benediktus Andra Pratama Dewanto (Business Accounting Review, 2016)
The purpose of this study was to examine or test the affect of transformational leadershipon financial performancethrough service qualityas the intervening variable on bank companies in Surabaya. Sample of this study was 35 bank companies in Surabaya. Data collected from Bursa Efek Indonesia by distributing questionnaire to the bank staff and client. This study used path modeling analysis technique with PLS tools. The results showed that there were positive and significant affects of transformational leadershipon financial performance, positive and significant affect of transformational leadershipon service quality, and also positive and significant affect of service quality on financial performance on bank companies in Surabaya.